Social Power Increases Interoceptive Accuracy - Moeini-Jazani, Mehrad; Knoeferle, Klemens; de Molière, Laura; Gatti, Elia; Warlop, Luk (Frontiers in Psychology, 2017)
Building on recent psychological research showing that power increases self-focused attention, we propose that having power increases accuracy in perception of bodily signals, a phenomenon known as interoceptive accuracy. Consistent with our proposition, participants in a high-power experimental condition outperformed those in the control and low-power conditions in the Schandry heartbeat-detection task. We demonstrate that the effect of power on interoceptive accuracy is not explained by participants’ physiological arousal, affective state, or general intention for accuracy. Rather, consistent with our reasoning that experiencing power shifts attentional resources inwards, we show that the effect of power on interoceptive accuracy is dependent on individuals’ chronic tendency to focus on their internal sensations. Specifically, we show that the effect of having power on interoceptive accuracy is stronger (vs. weaker) among individuals with a lower (vs. a higher) chronic tendency to focus on internal sensations. Finally, we demonstrate that individuals’ chronic sense of power also predicts interoceptive accuracy similar to, and independent of, how their situationally induced feeling of power does. We, therefore, provide further support on the relation between power and enhanced perception of bodily signals. Our findings provide initial evidence for the causal connection between social power and interoceptive accuracy and offer a novel perspective – a psychophysiological account- on how power might affect judgments and behavior. We highlight and discuss some of these intriguing possibilities for future research in the general discussion of this article.